Pengaruh Kompetensi Manajerial Terhadap Project Performance Pada Proyek Konstruksi Gedung di Jabodetabek - Fatih Nuurahman Putro Imansyah (Jurnal Teknologi Berkelanjutan, 2022)
Construction projects have different unique characteristics, are complex, and full of uncertainty, so a good management function is needed, including planning activities, implementation activities, and control activities. Not a few construction projects cause problems that have an impact on delays in project completion. Therefore, it is necessary to have a good project performance through four parameters, namely the right cost, on time, in accordance with the quality and safety so as to increase the satisfaction of stakeholders involved in the implementation of the project. This study aims to examine the influence of managerial on project performance. The number of respondents in this study were 112 respondents, all respondents were professionals who worked on building construction projects in Greater Jakarta (Jakarta, Bogor, Depok, Tangerang and Bekasi). The approach used in this study is a quantitative approach with an instrument in the form of a questionnaire. Research data obtained from the results of filling out the questionnaire were analyzed using the SEM PLS analysis technique with the help of the SmartPLS program. The results of this study indicate that managerial can affect project performance.